IMPROVING STUDENTS’ READING COMPREHENSION TROUGH SQ4R TECHNIQUE (A CLASSROOM ACTION RESEARCH AT SMP GENESIS MEDICARE CIMANGGIS-DEPOK) - Megawati Megawati (Sekolah Tinggi Pariwisata Mataram, 2023)
This research was aims to know students’ reading comprehension ability after the researcher was given treatement to the students. The students was given treatment by SQ4R technique. SQ4R technique means survey, question, read, reflect, recite and reviews. This research was conducted to SMP genesis Medicare Cimanggis Depok. The students was conducted eight grade. This research used Classroom Action Research Method. It was consists of three cycle. In every cycle, there are four steps. Planning, acting, observing and the reflecting. After researcher was conducted eight grade students, it was gotten in Cycle I there are 60% students pass KKM, and in Cycle II there are75 % students pass KKM then in Cycle III, there are 95 % students pass KKM. Students get improve in their reading comprehension trough SQ4R technique.